2017
DOI: 10.3310/hta21480
|View full text |Cite
|
Sign up to set email alerts
|

Duration of intravenous antibiotic therapy for children with acute osteomyelitis or septic arthritis: a feasibility study

Abstract: Declared competing interests of authors: Saul N Faust was UK chief investigator and University Hospital Southampton NHS Foundation Trust principal investigator for a Cubist-sponsored clinical trial of daptomycin against standard of care antibiotic therapy in paediatric osteomyelitis. All funds were paid into accounts within the NHS trust or university and not paid as personal fees. He reports consultancy fees for advisory board participation paid into accounts within the NHS trust or university (not personal f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 80 publications
1
16
0
Order By: Relevance
“…We showed that SA affects younger children more commonly than OM. S. aureus was the single most common causative agent of both OM and SA, which is consistent with a recent national cohort study 4. We found no clear difference between length of intravenous therapy and outcome.…”
Section: Discussionsupporting
confidence: 92%
“…We showed that SA affects younger children more commonly than OM. S. aureus was the single most common causative agent of both OM and SA, which is consistent with a recent national cohort study 4. We found no clear difference between length of intravenous therapy and outcome.…”
Section: Discussionsupporting
confidence: 92%
“…There are also studies with less than 6 weeks of total antimicrobial therapy, especially in the pediatric literature on hematogenous osteomyelitis. In this particular setting, a 3-week antibiotic course appears to be sufficient, as highlighted by many authors [29][30][31][32]. Among adults, 38 case series with antibiotic treatment durations of 3-4 weeks, including 5 to 36 patients each, revealed cure rates of approximately 80% according to a review published in 2005 [33].…”
Section: Discussionmentioning
confidence: 96%
“…There are also studies with less than six weeks of total antimicrobial therapy, especially in the pediatric literature for hematogenous osteomyelitis. In this particular setting, a three-week antibiotic course appears to be sufficient as highlighted by many authors [31][32][33][34]. For adults, 38 case series with antibiotic treatment durations of 3 to 4 weeks, including 5 to 36 patients each, revealed cure rates of approximately 80% according to a review published in 2005 [35].…”
Section: Discussionmentioning
confidence: 96%